HUBUNGAN MOTIVASI DAN KARATERISTIK DEMOGRAFI DENGAN KINERJA PERAWAT PUSKESMAS DI SUMBA TIMUR - ULY AGUSTINE (Poltekkes Kemenkes Kupang, 2016)
Introduction: One of the main strategies on health human resources development and empowerment is increasing their efficiency in work. Motivation and demographic characteristics is one of the factors that affect the performance of nurses. The objective of this research was to find out the correlation between motivation and demographic characteristics with the performance of nurses work in Public Health Center in East Sumba Regency. Method: This is a quantitative research with correlation study technique approach. The population of this research is 232 nurses in East Sumba Regency with 102 respondents as research sample who was taken by non purposive sampling. The data was analyzed using univariate and bivariat, using statistical test of chi-quare. Result: The research results are there is a significant correlation of demographic characteristics (age, education level and length of work) and the performance of nurses; there is a correlation of intrinsic motivation (responsibility, achievement, recognition, progress, evolve possibilities) and extrinsic motivation (salary, job security, working condition, supervision quality, interpersonal relationships among peers and superiors) with the performance of nurses on Public Health Center in East Sumba Regency. Conclusions: of this research are there is a significant correlation between motivation and demographic characteristics with nurses` performance; based on multivariate test, achievement sub-variable is the most significant correlation toward performance variable.